Original paperThe importance of exposure to contact allergens in patients with allergic contact dermatitis - Klimańska, Magdalena; Żmudzińska, Maria; Jenerowicz, Dorota; Czarnecka-Operacz, Magdalena (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
Introduction: Allergic contact dermatitis is a skin disease representing a type IV immunological reaction, also known as a delayed reaction, according to Gell and Coombs’ classification. It results from hypersensitivity to contact allergens and manifests itself as allergic contact dermatitis skin lesions. This clinical problem mainly affects adults and can be of occupational or non-occupational origin. Nowadays, there are more than 3000 recognised contact allergens which may be responsible for the development of allergic contact dermatitis. Hand dermatitis is the most common location of allergic contact dermatitis. Aim: The main purpose of this study was to evaluate the importance of exposure to contact allergens in allergic contact dermatitis patients. Moreover the detailed characteristics of sensitizing allergens in the examined group of patients are presented. Material and methods: Fifty patients in whom allergic contact dermatitis was diagnosed were enrolled in the study. The patients were also examined with the use of a questionnaire regarding exposure to contact allergens. Allergological diagnostics of type IV immunological reaction was performed according to mandatory procedures. Results: Nickel sulphate, cobalt chloride and potassium dichromate were acknowledged as the most common allergens in the examined group of patients. In the group of female patients, in contrast to the group of men, it was possible to indicate the allergen source which was responsible for developing or exacerbating allergic contact dermatitis skin lesions. Conclusions: The questionnaire results suggest that health education plays a crucial role in improving patients’ health status. Especially, it should be associated with giving detailed information to the patients concerning the possible sources of contact allergens in articles of daily use or those related to occupational or hobby activities. It would enable them to eliminate or at least limit exposure to the factors associated with development or exacerbation of allergic contact dermatitis symptoms.